Att ge förutsättningar för trivsel och arbetsglädje : Konflikthantering vid SSAB i Luleå - Johansson, Anna-Karin (2011)
The purpose of this thesis was to examine how conflict management works at SSAB in Luleå and to see if their goals and strategies mediate in a way that motivates employees to work actively with conflict management. The thesis only focuses on interpersonal conflicts within a specific group in the workplace. Through abduktiv method, where half structured interviews constituted the basis for a questionnaire survey to the employees, the following two questions were answered: How do the employees experience the function of conflict management? Are SSAB’s goals and strategies provided in a way that promotes motivation for the employees' to work with conflict management in a goal oriented way? The results showed that SSAB does not have any common goals or strategies for conflict management. The head of the workgroup that was the target of the survey had personal goals and a vision for the conflict management process as well as a strategy for how that work should be implemented. The employees’ experiences regarding conflict management pinpointed differences between the employees’. The results of the questionnaire survey showed that there are defectives in how the goals and strategies for conflict management are provided. Keywords: conflict, communication, motivation, goals, strategies. Validerat; 20110823 (anonymous)